Pandangan Muhammad Rizieq Shihab tentang Pancasila - Maula, M. Iqbal (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2019)
This paper seeks to describe the perspective of al-Habib Muhammad Rizieq bin Hussein Shihab on Pancasila. At the beginning of the paper will be explained in advance how the concept of the state. According to the Sharia is divided into two main ideas of textual-textual and substantial-contextual. Furthermore, it will be further elaborated on the debate in filling the ideology of the state of Islam and nationalist groups in the period of national movement. Then the author will describe the interpretation of al-Habib Muhammad Rizieq bin Husein Shihab in the interpreting of Pancasila with historical approach. Finally, the author critically examines this view which shows that the misinterpretation of al-Habib Muhammad Rizieq bin Hussein Shihab in understanding Pancasila.